Determinants of physical activity maintenance during the Covid-19 pandemic: a focus on fitness apps. Issue 4 (14th September 2020) - Yang, Yanxiang; Koenigstorfer, Joerg
Abstract : Individuals' overall physical activity levels decreased during lockdowns caused by the Covid-19 pandemic in the U.S. but fitness apps helped individuals remain active. Abstract: There are various health benefits of regular physical activity (PA) and health risks of sedentariness. The Covid-19 pandemic may have decreased PA and increased sedentariness for several reasons (e.g., closure of gyms, family-related time constraints, and reduced outdoor mobility). Yet, to date, there are no longitudinal studies that examined whether the pandemic affects PA levels and what factors help people remain physically active during lockdown. This study aims to investigate changes in U.S. residents' PA during (vs. before) the Covid-19 pandemic and predictors of changes, with a focus on PA smartphone applications (apps) and their features (i.e., motivational, educational, or gamification related). The study utilized a two-wave longitudinal survey design with an online panel. Healthy adults ( N = 431) from 45 U.S. states self-reported their PA levels before and during lockdown. PA app use and app feature ratings were assessed. t -tests and regression analyses were conducted. Moderate PA, vigorous PA, and PA measured in metabolic equivalent of task (MET) minutes per week decreased during lockdown (all p < .01). Controlling for PA before lockdown and individuals' PA intentions, PA app use was positively related to overall change in PA, measured in MET minutes per week (β = 15.68, standard error = 7.84, p < .05). PA decreased less with increasing app use frequency. When app features were added to the model, a buffering effect for gamification features was identified. The Covid-19-caused lockdown decreased U.S. residents' PA levels by 18.2%. The use of PA apps may help buffer the decline, and gamification-related app features may be particularly helpful in this context.